La filantropía femenina en la construcción de la ciudadanía: Semillas, una experiencia mexicana - Nathalie Ludec (Les Cahiers ALHIM)
How does philanthropy, and especially that by women, participate in the construction of citizenry ? Can philanthropy be a form for women to intervene in everyday democracy ? In order to answer this question, we will analyze the case of the association Semillas Sociedad Mexicana Pro Derechos de la Mujer A.C., which has its headquarters in Mexico DF. We will look into its activities, its book publications and the experiences of its members through the triple perspective of social class, gender and ethnicity.